Persepsi Masyarakat Terhadap Dampak Sosial, Ekonomi, dan Lingkungan Terhadap Keberadaan Hutan Tanaman Industri PT. Wirakarya Sakti (Community Perceptions of the Social, Economic, and Environmental Impacts of PT. Wirakarya Sakti’s Industrial Plantation) - Adzkia Chairunisa Ciptaningrum; Bramasto Nugroho; Leti Sundawati (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2026)
Limited timber supplies from natural forests have prompted the government to develop Industrial Plantation Forests to increase the productivity of production forests and meet the raw material needs of the timber industry. The presence of HTI affects the social, economic, and environmental conditions of the surrounding community. The purpose of this study is to analyze the impact of PT. Wirakarya Sakti’s industrial plantation forest on the social, economic, and environmental conditions of the community around the concession area. The study employed mixed-methods approach (qualitative and quantitative) through a survey. Quantitative data were obtained from 88 respondents determined using the Slovin formula with 10% margin of error. The data were analyzed using a paired sample t-test to compare conditions before and after the establishment of the HTI. Qualitative data were obtained through in-depth interviews and field observations. The positive impact of this study includes employment, the provision of social facilities, population migration, changes in community habits, increased community income, and the development of trade, service, and small businesses. The negative impacts of HTI operational activities include complaints about dust and noise from timber transportation, as well as potential conflicts related to land access and use. These findings confirm that the forestry sector provides tangible economic benefits to local communities, although it requires better management to minimize social and environmental impacts. This study enriches the literature on the impacts of industrial timber plantations, which can serve as a foundation for more sustainable management through collaboration of the government, companies, and the community.